Comitês de bacias hidrográficas de rios do Médio São Francisco: possibilidades e desafios de gestão do uso da água - Gomes, Claudia Salgado (2008)
This study has the waters as a theme managing the use of water, which have become increasingly scarce due to the incompatibility of the quantity and quality of water available with the growing demand of the population. Such shortage of this vital water resource, both in terms of quantity and quality, ends up triggering conflicts between different users. Facing such situation, this research aimed to study the problems and more frequent conflicts related to the water in the rivers of Médio São Francisco, in Minas Gerais, specifically the rivers Verde Grande, Riachão and Jequitaí, checking in which situations those issues culminate in the formation of Water Basin Committees, and in what extent they can tackle such issues. Thus, bibliographic and documental searches were conducted, as well as interviews in the cities of Belo Horizonte, Montes Claros and Bocaiúva, with 32 governmental and non-governmental agencies involved with the issue of water, as well as interviews with users. They were chosen intentionally, by trial and convenience. Several problems that contribute, directly or indirectly, to the shortage of water in rivers searched were identified. Such problems, in the most part are common to the three rivers, standing out the overthrow of native forest. The most frequent conflicts are those involving, on the one hand, medium and large farmers, who use irrigation systems that consume much water, and on the other hand, the small producers and the community, for whom just little water is left. These conflicts have been more evident in the river Riachão, which is due to the process of mobilization initiated by the communities living there, that pressured the responsible organs so that some solution was taken. It was evidenced that the Committees of Verde Grande and Jequitaí / Pacuí were created in order to solve the conflicts existing in Verde Grande and Riachão rivers respectively, but they have not managed to solve conflicts. One of the reasons is that these committees were not created on the basis of a request of the population of the water basin, which makes it difficult to recognize the same as a space to decide on the demands of society. Moreover, they are deliberative bodies and have no power to pressure and supervision. Among the difficulties for their action, there is in the Committees the lack of an administrative structure for the management, the lack of financial resources to enable them to implement the projects prepared, the lack of specialized human resources, as far in water resources management, as in management of conflicts, and, most importantly, the lack of popular participation. Possible solutions to the problems faced by Committees can be indicated, such as enabling human resources in management of water resources and management of conflicts, the consciousness of its members so that they can participate effectively in taking decisions and encouraging the popular participation.